"Experimental Studied of Density and Water absorption of Recycled Coarse Aggregate Concrete Incorporating GGBFS and FA". Issue 1 (January 2022) - Singh, Om Prakash; Kumar, Ravindra; Singar, Mahendra Kr.
Abstract: This investigates work the density and water absorption of concrete specimens cured at the age of 28 days. Natural coarse aggregate (NCA) has been replace with 60 percent, and 100 percent by RCA of construction & destruction (C&D) waste of 30-year-old building and Ordinary Portland cement (OPC) has been replaced with 10 GGBFS and FA. To understand the physical properties of concrete of normal weight test was perform and to find suitable results. To examine the water absorption properties of GGBFS and FA with recycled coarse aggregate (RCA) stand mix concrete at the age of 28 days. Based on the experiment's study, it can be brief that the 40 percent replacement of NCA with RCA carried excellent results with 20 percent GGBFS. This research presents the outcome of GGBFS and FA as a cement replacement on the physical properties of RCA.